Kajian Empiris Variabel Makroekonomi Dan Mikroekonomi Terhadap Beta Saham Pada Perusahaan Yang Terdaftar Di Kompas 100 Periode 2009-2013 - Caecilia, Carrolina; Cahyadi, Sendy (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractThis study analizes about the influence of macroeconomics and microeconomics variables towards stock of beta. The macroeconomics variables tested are inflation, interest rate, middle rate, gross domestic product, and money supply, while the microeconomics are asset growth, current ratio, debt to equity ratio, return on equity, and dividend payout ratio. The results are that out of 10 macroeconomics and microeconomics variables tested, only 8 passed the classical assumption test. Simultaneously (F test), 8 variables that passed affects stock of beta simultaneously. Partially (t test), only interest rate and current ratio has a positive significant effect.